Physiological responses of plants to attack - Walters, Dale R. (Wiley Blackwell, 2015)
Despite the research effort put into controlling pathogens, pests and parasitic plants, crop losses are still a regular feature of agriculture worldwide. This makes it important to manage the crop appropriately in order to maximise yield. Understanding the relationship between the occurrence and severity of attack, and the resulting yield loss, is an important step towards improved crop protection. Linked to this, is the need to better understand the mechanisms responsible for reductions in growth and yield in affected crops